2021
DOI: 10.3390/v13091814
|View full text |Cite
|
Sign up to set email alerts
|

A Bioluminescent 3CLPro Activity Assay to Monitor SARS-CoV-2 Replication and Identify Inhibitors

Abstract: Our therapeutic arsenal against viruses is very limited and the current pandemic of SARS-CoV-2 highlights the critical need for effective antivirals against emerging coronaviruses. Cellular assays allowing a precise quantification of viral replication in high-throughput experimental settings are essential to the screening of chemical libraries and the selection of best antiviral chemical structures. To develop a reporting system for SARS-CoV-2 infection, we generated cell lines expressing a firefly luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…BAY2402234 is a novel potent selective DHODHi with an IC 50 of 1.2 nM [ 86 ]. Mathieu et al screened 492 compounds inhibiting SARS-CoV-2 replication and found that BAY2402234 blocked almost 100% of SARS-CoV-2 particle production at 0.6 μM [ 87 ]. In addition, the combination of teriflunomide, IMU-838/vidofludimus, and BAY2402234 inhibited SARS-CoV-2 replication and reduced viral yield by at least two orders of magnitude in Vero E6 and Calu-3 cells infected with wildtype, the Alpha variant, and the Beta variant of SARS-CoV-2 [ 88 ].…”
Section: Dhodhi Applications In Antiviral Treatmentmentioning
confidence: 99%
“…BAY2402234 is a novel potent selective DHODHi with an IC 50 of 1.2 nM [ 86 ]. Mathieu et al screened 492 compounds inhibiting SARS-CoV-2 replication and found that BAY2402234 blocked almost 100% of SARS-CoV-2 particle production at 0.6 μM [ 87 ]. In addition, the combination of teriflunomide, IMU-838/vidofludimus, and BAY2402234 inhibited SARS-CoV-2 replication and reduced viral yield by at least two orders of magnitude in Vero E6 and Calu-3 cells infected with wildtype, the Alpha variant, and the Beta variant of SARS-CoV-2 [ 88 ].…”
Section: Dhodhi Applications In Antiviral Treatmentmentioning
confidence: 99%
“…Several methods have been developed or adapted for quantifying the potency of the SARS-CoV-2 M-pro inhibitors [ 73 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. These methods demonstrate the mechanism of action of antiviral drugs and do not require cells infected with SARS-CoV-2 or a laboratory with biosafety level 3 containment facilities.…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
“…However, this C-terminal His-tag can lower the binding affinity of a given ligand [ 90 ]. To overcome the limitations of the in vitro screens, cell-based assays have been developed [ 73 , 80 , 83 , 84 , 87 , 88 ]. In these assays, the cells express the M-pro and the reporter used and can differentiate cytotoxicity from true M-pro inhibition [ 83 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
“…Intracellular 3CLpro activity has previously been detected in SARS-CoV-2-infected human cell lines [ 32 , 33 ], but it remains to be determined whether the in vitro AuNP protease assay is sufficiently sensitive to detect cellular 3CLpro activity from SARS-CoV-2 infected human cell line lysates. Protein levels of 3CLpro appear to be 50-fold lower in the context of viral infection, compared with transient transfection of the protease as an exogenous transgene ( Supplementary Figure S9 ).…”
Section: Discussionmentioning
confidence: 99%